Assessment of lipid profile when using lipid-lowering therapy (statins) in patients with coronary atherosclerosis - N. E. Gavrilova; V. A. Metelskaya; E. B. Yarovaya; N. V. Gomyranova; S. A. Boytsov (Рациональная фармакотерапия в кардиологии)
Aim. To assess of lipid-lowering therapy with statins in very high cardiovascular risk patients admitted to hospital for coronary angiography and analyze lipid profiles depending on the intensity of lipid-lowering therapy. Material and methods. A total of 502 patients aged 25-86 years (mean age 61.2±9.4 years) who admitted to the clinic of State Research Center for Preventive Medicine were consecutively included into the study. All of them were examined and underwent coronary angiography. Plasma lipid levels were determined by standard laboratory methods. Results. The levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-cholesterol) and non-high-density lipoprotein cholesterol (HDL-cholesterol) were significantly higher among patients not taking lipid-lowering therapy. 62.1% of patients having a non-intensive lipid-lowering therapy and 52.5% of the patients having intensive therapy reached the target level of TC for high-risk patients. However, only one third of patients reached the target TC level for patients at very high risk in these patient groups. Target level of LDL-cholesterol <1.8 mmol/l among all patients was reached only in 11.2% of patients treated with low doses and in 12.7% of patients treated with high doses of lipidlowering drugs. Conclusion. Dyslipidemia management in real clinical practice remains suboptimal, with a substantial proportion of patients fails to achieve guideline-recommended target lipid levels to reduce the risk of cardiovascular diseases and their complications.